Translation Shift Found in Gadis Kretek Novel - PUJA ASTUTI, NI PUTU; Pratiwi, Putu Ayu Asty Senja; Sukarini, Ni Wayan (International Journal of Linguistics and Discourse Analytics, 2025)
This study investigates translation shifts in Gadis Kretek by Ratih Kumala and its English translation Cigarette Girl, translated by Annie Tucker. Using a descriptive qualitative approach and drawing on Catford’s (1965) theory of translation shifts, the research examines linguistic changes that occur in the translation process from Indonesian into English. The findings identify two major types of translation shifts: level shifts and category shifts. Level shifts involve changes between grammatical and lexical levels, while category shifts comprise structural, class, unit, and intra-system shifts. These shifts demonstrate the translator’s strategies in addressing systemic differences between Indonesian and English to achieve naturalness, clarity, and semantic equivalence in the target text. The study highlights the practical role of translation shifts in enhancing textual readability without compromising the source text’s meaning. By illustrating how Catford’s shift theory operates in a contemporary literary context, this research contributes to translation studies and offers useful insights for literary translators dealing with cross-linguistic and structural challenges.